Perilaku Guru Dalam Pembelajaran Berbasis Nilai Ibadah Di SMP IT Nurul Ilmi Medan Estate - Rini Rini Dewi Andriani (Pascasarjana UIN Sumatera Utara, 2020)
Based on Law no. 20 of 2003 article 3 concerning the National Education System that national education functions to develop capabilities and shape the character and civilization of a dignified nation in the context of educating the nation's life, aiming to develop the potential of students to become human beings who believe and fear God Almighty, have noble character. , healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. Integrated Islamic School (SIT) is more dominant in its religious character education. One of the schools that has implemented religious character education through school culture is SMP IT Nurul Ilmi Medan Estate. It can be seen in the vision of this school, namely